Land Utilization After Land Occupation: A Case of Peasant Movement in Nanggung District, Bogor Regency, Indonesia - Assiyah, Ai Siti Nur; Shohibuddin, Mohamad (Jurnal AGRISEP, 2025)
One of the key challenges faced by the peasant movement after occupying disputed land is optimizing its utilization to support sustainable livelihoods. This study investigates land utilization practices following the occupation of abandoned plantation concession in Nanggung District, Bogor Regency. Of the 37 occupied land blocks across three villages in the district, this study focuses on a single block located in Cisarua Village. Employing a mixed-method approach, quantitative data were collected through a census survey of 47 farming households managing land in the selected block, complemented by qualitative data from in-depth interviews and field observations. The findings reveal diverse land utilization orientations—ranging from commercial and subsistence farming to non-agricultural activities—and substantial variations in commodity production and farm income. This diversity is primarily shaped by two factors: (1) individual respondent characteristics, notably farming experience, and (2) household characteristics, particularly landholding size. These findings underscore the importance of improving post-occupation support systems to ensure that land reform leads to long-term socio-economic benefits for peasant households.